The Position of Adat Law in the Indonesian Criminal Code Which Adheres to Legality Principle - Clara Mega Kharisma Sari; Mohammad Jamin (Program Pascasarjana Fakultas Hukum Universitas Sebelas Maret Surakarta, 2024)
On 6 December 2022, it was approved that law number 1, the year 2023 about Indonesia’s criminal code (KUHP) has been implemented since the day of approval. This is an effort of legal politics to solve the problems in the community nationally and patriotically. In law number 1, the year 2023 which still adheres to the principle of legality has become a problem where the principles are different from the Adat (customary) law which is written. The position of Adat law should be elaborated concretely so that multi-interpretation does not happen because Indonesia is an archipelago meaning that it has many islands with various tribes and cultures. Besides, the mechanism guideline for the system of the Adat criminal court has not been adjusted yet. With the case in mind, the researcher used normative juridic methodology to identify the research questions using a conceptual approach related to the position of Adat Law in law number 1, the year 2023 that adheres to legality principle, analyze the implementation of legality principle, and the regulations related to the current problems. The data gathered were primary data, secondary, and tertiary. The findings showed that it was important to be concerned about the society’s aspirations in making operational procedures from the various policymakers including the Adat community, Adat authority, the organization of Adat law, and the activists of Adat law. That should be done to make sure that involving Adat Law in the National Law system can represent the spirits and wishes of Indonesians to reach Expediency, Justice, and Certainty for the people.